(A-LIEP 2011): Information Behavior of Journalists: Analysis of Critical Incidents of Information Finding and Use / Abdus Sattar Chaudhry and Luluwa Al-Sagheer - Chaudhry, Abdus Sattar; Al-Sagheer, Luluwa (2011)
This study is aimed at investigating information behavior of journalists in Kuwait. It attempted to seek answers to questions such how search for information is initiated, what information sources are preferred and how successful is information finding activity? Journalists were asked to report critical incidences of information finding related to their recent journalistic assignment through a questionnaire. Analysis of 42 critical incidents indicated that journalistic assignments were in four major areas: political, cultural business, and sports. In most cases, background information was most frequently sought type of information. Internet was the most frequently used information source even though some journalists perceived that information available on the various web sites may not be very objective. A follow up study is planned to be carried out to discuss the findings with a selected group of journalists using focus group discussions.